Atlas of heart disease and stroke among American Indians and Alaska Natives - National Center for Chronic Disease Prevention and Health Promotion (U.S.)
A Message from the Director of CDC -- A Message from the Director of IHS -- Foreword -- Section 1. Introduction -- Section 2. National maps of heart disease and stroke mortality among American Indians and Alaska natives -- Section 3. Risk factors for heart disease and stroke among American Indians and Alaska natives, by State -- Appendix A. Risk factors for heart disease and stroke among the total U.S. population, by state -- Appendix B. Methodological and technical notes -- Appendix C. Resources Michele L. Casper, Clark H. Denny, Jonathan N. Coolidge, G. Ishmael Williams, Jr., Amanda Crowell, James M. Galloway, Nathaniel Cobb. Also available via the World Wide Web. Casper ML, Denny CH, Coolidge JN, Williams GI Jr, Crowell A, Galloway JM, Cobb N. Atlas of Heart Disease and Stroke Among American Indians and Alaska Natives. Atlanta, GA: U.S. Department of Health and Human Services, Centers for Disease Control and Prevention and Indian Health Service; 2005.